Implementation of Informed Consent at Bandung Hospital, Medan City - Sitepu, Fadel; Isnaini, Isnaini; Akmal, M. Ridha Haykal (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the implementation of informed consent as a legal protection mechanism in medical practice at Bandung General Hospital, Medan City. The method used is normative legal research with a normative legal approach, utilizing secondary data from primary, secondary, and tertiary legal materials, as well as field data through interviews and surveys. The results of the study indicate that the implementation of informed consent at the hospital has followed the standard operating procedures regulated by the Minister of Health Regulation No. 290/MENKES/PER/III/2008. The informed consent process involves providing comprehensive information, consideration time for patients, and documentation of written consent. However, there are several challenges, including time constraints, ineffective communication, and low levels of patient health literacy. This study suggests improving communication training for medical personnel, providing patient education tools, and improving the documentation system to ensure legal compliance and quality of health services. Effective implementation of the informed consent procedure has the potential to improve legal protection for medical personnel and patient rights in medical decision-making.